2016
DOI: 10.2147/copd.s117626
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Anxiety Inventory for Respiratory Disease in patients with COPD in China

Abstract: BackgroundAnxiety is a common comorbidity in patients with COPD in China, and it can significantly decrease patients’ quality of life. Almost all anxiety measurements contain somatic items that can overlap with symptoms of COPD and side effects of medicines, which can lead to bias in measuring anxiety in patients with COPD. Therefore, a brief and disease-specific non-somatic anxiety measurement scale, the Anxiety Inventory for Respiratory Disease (AIR), which has been developed and validated in its English ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Chronic obstructive pulmonary disease (COPD), as a major worldwide health problem, is characterized by persistent airflow limitation which is usually progressive and associated with an enhanced chronic inflammatory response in the airway and the lung to noxious particles or gases [ 1 , 2 ]. The World Health Organization (WHO) has estimated that it will increase to being the third leading cause of death, making this a global epidemic by 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD), as a major worldwide health problem, is characterized by persistent airflow limitation which is usually progressive and associated with an enhanced chronic inflammatory response in the airway and the lung to noxious particles or gases [ 1 , 2 ]. The World Health Organization (WHO) has estimated that it will increase to being the third leading cause of death, making this a global epidemic by 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common comorbidity in patients with COPD 16. Studies report that depression may cause worsening of the quality of life, social isolation, physical impairment, prolonged hospitalization, and increased risk of mortality 17,18. Recent reviews have reported that 25% of COPD patients have some degree of depression 19.…”
mentioning
confidence: 99%
“…Therefore, although the usual community structures are disrupted by behaviors or dexterity, stronger community structures and more positive functioning can emerge in the community [32]. Practice disease prevention Corona, the new target is the social life of the people affected, and makes people feel that compliance with them can be not only the health of the body, which They should also dominate the health of the society and see themselves as the rulers of the conditions and not the victims.…”
Section: Discussionmentioning
confidence: 99%